Skill Gap, Mismatch, and the Dynamics of Italian Companies' Productivity - Lucrezia Fanti; Dario Guarascio; Matteo Tubiana (Global Labor Organization (GLO), 2019)
Relying on a unique integrated database, this work explores the relationship between labour productivity, on one side; intensity and characteristics of companies' skills need and degree of skill mismatch, on the other. The analysis focuses on a representative sample of Italian limited liability companies observed during the years 2012, 2014 and 2017. First, companies acknowledging the need to update their knowledge base display a higher productivity vis-à-vis other firms. Second, when it comes to the skill need distinguished by competence/knowledge domains (management, STEM, social and soft skills, technical operatives and humanities) it emerges that companies looking for technical operative and social skills show lower labour productivity as compared to other firms. On the contrary, companies characterized by a need in managerial, STEM or humanities-related skills show higher productivity. Third, the ability to match the skill need via new hiring is always positively correlated with firms' productivity. This result is confirmed across all the adopted specifications.
Keywords: D22; D80; J24; 330; labour productivity; skill mismatch; firm-level heterogeneity; knowledgebase; organizational capabilities